PENGOMPOSAN DAN EFEK KOMPOS SERASAH DAUN ACASIA MANGIUM L TERHADAP PERTUMBUHAN DAN PRODUKSI KACANG TANAH - Djukri, Djukri (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2005)
The objective  of the research  is to investigate  the effect of the Acasia mangium  L leaves rubbish  compost  on the growth and production  of peanut.The  peanut    used    is gajah  variety.  The Acasia  mangium   L leaves rubbish  compost   was  used  for  the  treatment   materials     given  since   the seedling  time.  The  compost   was  mixed  with  the  soil    used  for  planting media.  This  research   applied  the  Completely   Randomized   Design  (CRD). The independent  variables  consisted  of six levels i.e 0,10, 20, 30, 40, and 50 grams compost  per  polibag,  each five replications.  The dependent  variables are height, fresh weight,  dry weight  at the end of the vegetative  growth,  and the sum of the  fruit  is counted  after  harvest.  The data  were analyzed  using the analysis of variants  (anova),The  result  of  the  research   indicates  that  after    receiving  treatment,the height, fresh weight,  and dry weight  of peanut,  on 30, 40, and 50 grams proportion  of the  compost  weight  are  significant  (p<0.05).  The  sum  of the ghost on 40 and 50 grams proportion  of compost  weight,  shows a significant result (p<0.05).  The combination   of the height, fresh weight, and dry weight parameters     on  30,  40,  and  50  grams  compost   weight,   shows   value   of growth better than with other treatments.Key words: composting, growth, and production